LITERATUR REVIEW : DUKUNGAN SOSIAL BAGI ANAK DENGAN KEDISABILITASAN - Alfia Fadhila Husna; Hastin Trustisari (JOURNAL SAINS STUDENT RESEARCH, 2025)
Social support is crucial for the development of children with disabilities. Children with disabilities often face challenges such as negative stigma, social interaction difficulties, and self-care challenges. This study aims to analyze the forms of social support and its impact on the development of children with disabilities through a literature review. The method used is a descriptive literature review, searching Google Scholar for the keywords "social support for children with disabilities" published between 2015-2025. A total of 15 relevant articles were analyzed to provide a comprehensive overview of the topic. The results show four main forms of social support from families: emotional, instrumental, informational, and esteem. This support can enhance social functioning, self-confidence, and independence, as well as motivate them to achieve. Although the family is the primary source, the role of teachers is also significant in a school context. The implication is the need for family capacity-building programs and collaboration among families, schools, and communities to build a comprehensive support ecosystem for children with disabilities.